2017
DOI: 10.5194/acp-17-13681-2017
|View full text |Cite
|
Sign up to set email alerts
|

Biomass burning emissions in north Australia during the early dry season: an overview of the 2014 SAFIRED campaign

Abstract: Abstract. The SAFIRED (Savannah Fires in the Early Dry Season) campaign took place from 29 May until 30 June 2014 at the Australian Tropical Atmospheric Research Station (ATARS) in the Northern Territory, Australia. The purpose of this campaign was to investigate emissions from fires in the early dry season in northern Australia. Measurements were made of biomass burning aerosols, volatile organic compounds, polycyclic aromatic carbons, greenhouse gases, radon, speciated atmospheric mercury and trace metals. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 62 publications
4
26
0
1
Order By: Relevance
“…A detailed description of the campaign, the site, and all the instruments deployed is available in the overview manuscript by Mallet et al []. Components of interest with regard to this manuscript are presented below:…”
Section: The Safired Campaign and Instrumentationmentioning
confidence: 99%
See 4 more Smart Citations
“…A detailed description of the campaign, the site, and all the instruments deployed is available in the overview manuscript by Mallet et al []. Components of interest with regard to this manuscript are presented below:…”
Section: The Safired Campaign and Instrumentationmentioning
confidence: 99%
“…Figures and show the time series of trace gases and Aitken and accumulation aerosol size modes recorded during the campaign. Those figures also denote the four biomass burning periods (BBP) identified by Mallet et al [] and nine strong smoke events (A to I) identified as part of this study (see Table ).…”
Section: Atmospheric Composition and Meteorology During The Safired Cmentioning
confidence: 99%
See 3 more Smart Citations